Determination of Antioxidant Activity of Stem Bark (Manihot esculenta Crantz) by 1,1-Diphenyl-2-picrylhydrazyl (DPPH) Scavenging Method - Latu, Saparuddin; Jangga, Jangga; Mansur, Mansur; Gajali, Nurdila (Pharmaceutical Reports, 2023)
Cassava bark is a part of the cassava plant which is still underutilized besides being used as animal feed and wasted as waste. Each cassava can usually produce 10-15% cassava bark. The amount of waste produced can cause accumulation, resulting in environmental damage if not appropriately utilized. This research aims to determine the antioxidant activity of cassava bark (Manihot esculenta Crantz) using the DPPH (1,1-diphenyl-2-pikrihidrazil) method, measured using a UV-Vis spectrophotometer. Extraction used the maceration method of 96% ethanol as solvent. The determination of antioxidants in ethanol extract of cassava bark by the DPPH method and using vitamin C was used as a reference. Vitamin C was made in four series of concentrations, namely 2, 4, 6, and 8 ppm, while the ethanol extract of cassava bark was 20, 40, 60, and 80 ppm. From several concentration series, 2 ml was taken, and 1 ml of 50 ppm DPPH was added; then, the mixture obtained was incubated for 30 minutes in a place protected from light. The absorbance was measured at a wavelength of 515 nm. The results showed that the ethanol extract of cassava bark has a potent antioxidant activity based on the IC50 value obtained, which is 3.847 mg/L. Therefore, the ethanol extract of cassava bark can be developed as a natural antioxidant.